Use of pharmacological therapy localized in periodontics: Literature review (Research, Society and Development, 2022)
When the microorganisms are eliminated before the pathological evolution occurs, the periodontal tissues return to their normality, however, impacts after treatment such as bone loss are still possible. In this sense, the control and maintenance of oral hygiene is a determining factor for therapeutic success, however, factors such as tobacco and stress are associated with failure. Even so, limitations such as access in furcation regions, reservoir of bacteria in the dentinal tubules, deep pockets and even concavities, can facilitate the recolonization of bacteria after mechanical treatment. In this perspective, the present study aims to gather and report the drugs used as local therapy in periodontics, as well as present their advantages and disadvantages, in order to understand the best pharmacotherapeutic applicability. In this way, it is understood that treatment with local drugs is an essential factor for success in periodontal treatment, since only mechanical control and the presence of factors such as tobacco and stress make the treatment inefficient. Furthermore, further studies are needed to better prove the therapeutic efficacy.